Definitions of non-response and response to biological therapy for severe asthma: a systematic review - Ekaterina Khaleva; Anna Rattu; Chris Brightling; Andrew Bush; Arnaud Bourdin; Apostolos Bossios; Kian Fan Chung; Rekha Chaudhuri; Courtney Coleman; Ratko Djukanovic; Sven-Erik Dahlén; Andrew Exley; et al. (ERJ Open Research, 2023)
Background Biologics have proven efficacy for patients with severe asthma but there is lack of consensus on defining response. We systematically reviewed and appraised methodologically developed, defined and evaluated definitions of non-response and response to biologics for severe asthma. Methods We searched four bibliographic databases from inception to 15 March 2021. Two reviewers screened references, extracted data, and assessed methodological quality of development, measurement properties of outcome measures and definitions of response based on COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN). A modified GRADE (Grading of Recommendations Assessment, Development and Evaluation) approach and narrative synthesis were undertaken. Results 13 studies reported three composite outcome measures, three asthma symptoms measures, one asthma control measure and one quality of life measure. Only four measures were developed with patient input; none were composite measures. Studies utilised 17 definitions of response: 10 out of 17 (58.8%) were based on minimal clinically important difference (MCID) or minimal important difference (MID) and 16 out of 17 (94.1%) had high-quality evidence. Results were limited by poor methodology for the development process and incomplete reporting of psychometric properties. Most measures rated “very low” to “low” for quality of measurement properties and none met all quality standards. Conclusions This is the first review to synthesise evidence about definitions of response to biologics for severe asthma. While high-quality definitions are available, most are MCIDs or MIDs, which may be insufficient to justify continuation of biologics in terms of cost-effectiveness. There remains an unmet need for universally accepted, patient-centred, composite definitions to aid clinical decision making and comparability of responses to biologics.